The High Cost of Death After Acute Myocardial Infarctions: Results from a National US Hospital Database - Mallow PJ; Browne F; Shemisa K (ClinicoEconomics and Outcomes Research, 2023)
Peter J Mallow,1 Frederick Browne,1 Kamal Shemisa2 1Health Services Administration, Xavier University, Cincinnati, OH, USA; 2TriHealth Heart Institute, Cincinnati, OH, USACorrespondence: Peter J Mallow, Email mallowp@xavier.eduIntroduction: This study described the differences in costs and length of stay (LOS) among patients with AMI who died versus survived using a large, nationally representative cohort of AMI patients.Methods: The 2019 HCUP NIS was used to analyze costs, and LOS among all patients with a principal diagnosis of AMI. A propensity-score matched analysis and multivariable regression were used to adjust for patient and hospital characteristics.Results: There were 4559 visits in each of the cohorts (total 9118). The adjusted mean hospital cost was $18,970 (95% CI $16,453 - $21,871) for those that survived and $23,173 (95% CI $20,167 - $26,626; p < 0.001) for those that died. The LOS was 3.95 (95% CI 3.41– 4.57) in survivors and 4.24 (95% CI 3.67– 4.89; p < 0.001) in those who died.Conclusion: Survivors of AMI incurred lower costs and length of stay than those who died. Higher costs were attributed to greater LOS and higher-level care. The results suggest that economic evaluations of cardiovascular interventions that do not include the cost of dying may underestimate the benefits of the intervention.Keywords: acute myocardial infarction, healthcare utilization, mortality, cardiovascular